Analysis of Effects of precession mechanism error on polishing spot for bonnet polishing. (January 2018) - Yang, Xu; Wang, Zhenzhong; Wang, Chunjin; Peng, Yunfeng
In this article, a research was conducted on the effects of the precession mechanism error on polishing spot, and it is helpful for optimizing the mechanism. In the research, an error model was built to analyze the error caused by gravity and polishing force on the accuracy of the mechanism, finite element analysis and MATLAB simulation were carried out based on the error model to estimate the effects, and, finally, an experiment was conducted to test the simulation result. It was found that the precession mechanism error mainly has an influence on the position of polishing spot in x and y directions. Simulation results show the position error up to −698.7 µm in y direction and −88.5 µm in z direction under free condition, while in polishing process, the error decreased 588.4 µm in y direction and 26.7 µm in z direction. The size of single polishing spot decreased 2.67%, while the size of four-step tilted polishing spot and continuous polishing spot increased 0.66% and 6.78%, respectively. Through experiment, it can be seen that the size of the polishing spot is also affected by the inflation pressure in bonnet tool, rigidity of bonnet tool, tool clamping error, and mechanism processing error.